PENERAPAN METODE MULTI-ATTRIBUTE UTILITY THEORY DALAM PEMILIHAN PENERIMA BANTUAN SOSIAL JASA PELAYANAN PUBLIC PENGABDIAN KEPADA MASYARAKAT TERDAMPAK COVID-19 (Universitas Methodist Indonesia, 2022)
Community Service Fund Assistance Government assistance, one of which is assistance to the community with government assistance in the form of Community Service Fund Assistance, is an institution engaged in community service. determine community members. services affected by Covid-19 to be right on target. This is due to the absence of a systematic and measurable system for determining eligible communities as recipients of service fund assistance. Starting from recording, recapitulating, and making reports which are still being carried out one by one, the accuracy of the data becomes less. where decisions are taken from several criteria, namely: the occupation of the population, monthly income, place of residence, and main source of information. by comparing alternatives based on each criterion. This results in a decision to choose community service funding assistance. Decision Support System for Accepting Community Service Funds Using Death (Multi-Attribute Utility Theory) as a decision support system so that the sub-district can easily select residents from predetermined criteria. Then to get more accurate results, it is necessary to test the validity of alternative comparisons that are more appropriate in accordance with the needs for selecting the eligibility of recipients of social funds for residents affected by Covid-19.